They meet, they talk … but nothing changes: Meetings as a focal context for studying change processes in organizations - Klonek, Florian; Paulsen, H.; Kauffeld, S. (2015)
In this chapter, we discuss how meetings relate to organizational change management. We present a coding instrument that assesses meeting talk in terms of change or sustain talk, two psycholinguistic constructs that are supposed to facilitate or inhibit organizational changes and that represent participants' readiness versus their resistance to change. We present a step-by-step guideline on how the dynamics of readiness and resistance to change within one meeting can be graphed using a time-sensitive measure that we call the R-index (i.e., for readiness and resistance to change). We show how two theoretical frameworks – Lewin's field theory and the transtheoretical model of change – are related to the operationalization of change talk and sustain talk in meetings. Finally, we discuss how the R-index can be used as a dynamic measure of change readiness in meetings.